The Effect of Fluency Oriented Reading Instructionon EFL Students’Reading Fluency and Comprehension - BOUGUEBS, Radia (Journal of Human Sciences, 2017)
This paper discusses and examines the effects of a fluency reading instruction cycle onstudents’ progress in there ading skill. To reach this objective, the study implemented the Fluency Oriented Reading Instruction (FORI) approach, a research-based integrated fluency routine framework, to determine if the components of reading fluency (automaticity, word recognition accuracy, prosody, and comprehension) improve. The present research was conductedatthe department of English in the ENS-C where an experimental pretest-posttest with control group design was used. Pretest and posttests of reading fluency, reading comprehension and reading prosody were administered, and a t test was used to compare the means of correct word per minute (CWPM), prosody, and comprehension within an experimental group and a control group. The results indicated that the FORI is an effective approach to improve students’reading fluency and comprehension as demonstrated by CWPM improvement, prosody gains, and comprehension achievements as well.